Machine Learning with R - Lantz Brett (Packt Publishing, 2013)
Written as a tutorial to explore and understand the power of R for machine learning. This practical guide covers all of the need to know topics in a very systematic way. For each machine learning approach, each step in the process is detailed, from preparing the data for analysis to evaluating the results. These steps will build the knowledge you need to apply them to your own data science tasks. Intended for those who want to learn how to use R's machine learning capabilities and gain insight from your data.